Sundanese Local Wisdom: Spirit in Management of Village Fund Budget - Nurul Rusdiansyah; Silvia Sarikuswati (Westscience Press, 2023)
The purpose of this study is to explore the values of Sundanese wisdom in relation to Village Fund budget management as an effort to minimize the risk of fraud. The research method used in this research is qualitative method with realist ethnographic approach. Research findings show that the philosophical basis for village fund management in Talaga village is the values of local wisdom such as kudu silih asih, silih asah jeung silih asuh, prohibition ulah nyolok mata buncelik in the planning stage, Organized ngeduk cikur kedah mitutur, nyokel jahe kedah micarek, recommendations cikaracak ninggang batu, laun-laun jadi legok in the implementation and administration stages, and recommendations kudu nyanghulu ka hukum, nunjang ka nagara, mupakat ka balarea in the reporting and budget accountability stages Dana Desa.